ISpring application-based volleyball game learning media development - Ichwan Fauzi; Hariyoko Hariyoko (Universitas Negeri Malang, 2023)
Background: Learning media is one of the essential factors in achieving learning objectives, so a subject requires appropriate learning media. Objective: This research aims to develop a volleyball game learning media for students in class VIII at State Junior High School 9 Malang. Methods: This research uses the Research and Development method ADDIE. As for the data collection instrument in the form of observation by directly observing learning activities in class VIII State Junior High School 9 Malang, namely learning volleyball games, the time is relatively short, so the teacher needs help giving students the material as a whole. Results: This research has gone through three validations, including volleyball game learning experts with an average of 74.30%, learning media experts with an average of 98.95%, and physical education, sports, and health teachers with an average of 97.5%. Then, the results of the overall product trial involving 45 class VIII students of State Junior High School 9 Malang were divided into two small group trials, with 15 students getting a result of 87.93% and the large group tryout of 30 students getting a result of 86.5%, from the results obtained it was declared very feasible. Conclusion: Based on the results of the above research, namely the product of learning media for volleyball games with the ISpring application for class VIII students of State Junior High School 9 Malang, it is included in the criteria of being very suitable for learning volleyball games.